MENAKAR BUDAYA DEMOKRASI MASYARAKAT LOKAL DI PROVINSI SULAWESI BARAT DALAM ERA DIGITAL - Rasyid, Suraya; Usman Jafar (ISTIQRA: Jurnal Hasil Penelitian, 2024)
This research aims to measure the democratic culture of local communities in West Sulawesi Province in the Digital Era. This research uses a qualitative method with a phenomenological approach, the data sources in the research are primary data sourced from interviews and observations and secondary data sourced from literature studies both from journals and books related to the research objectives. Data collection techniques were carried out through focus group discussion (FGD) activities. After the data is collected, the next step is data analysis to produce conclusions. The results of this research are that the local community in West Sulawesi Province is the Toliutang community who live on one of the islands in Mamuju Regency, West Sulawesi Province. Even though this tribe lives on the sea and depends on the open sea for their livelihood, they secretly have quite good democratic behavior and culture. The use of digital technology in developing political culture and democracy is starting to become embedded in their lives. One of these values ​​is helping each other and humanizing humans. These are all values and belief systems held in society. So political activity is used as a means of fulfilling the basic needs of citizens in creating mutual benefits. In the future, the political participation shown by the Toliutang community or tribe will be biased because the behavior of the political elite is not balanced in realizing improvements in people's lives as a consequence of political responsibility towards the people, but is ignored and forgotten